Quality of life among parents of autistic children: questionnaire validation study and multivariate analysis of associated factors - Konowałek, Łukasz; Kotowska-Bąbol, Maja; Łukasik, Jan; Remiszewski, Piotr; Wolańczyk, Tomasz (Frontiers in Psychiatry, 2025)
Parents of children with autism often experience unique challenges that can impact their emotional wellbeing. The aim of this study was to validate the Polish adaptation of the Quality of Life in Autism Survey (QoLA) and to examine the factors influencing quality of life (QoL) among parents of children with autism spectrum disorder (ASD). The survey was administered to 372 participants, predominantly mothers, and assessed QoL using the QoLA-A and QoLA-B scales alongside established tools such as the Beck Depression Inventory and WHOQOL-BREF. Results showed high reliability for the QoLA-A scale, supported by Cronbach's alpha (0.93) and omega coefficients, and confirmed an 8-factor model consistent with Schalock's domains of QoL. The scale showed strong correlations with psychological health, social relationships and environmental factors, validating its criterion and construct reliability. Conversely, QoLA-B showed limitations, capturing only five dimensions and explaining less than 50% of the variance. Important predictors of parental QoL included employment status, material well-being and depressive symptoms, with externalising behaviours in children having a significant negative influence. Intellectual and communication disabilities, although a significant challenge, were not strongly correlated with parental QoL. The findings highlight the need to address socio-economic and mental health support for caregivers, with an emphasis on tailored interventions that enhance parental wellbeing, rather than exclusively targeting child-specific therapies. This comprehensive validation highlights the utility of the QoLA-A and the nuanced factors that influence caregiver QoL.